1993
DOI: 10.1007/bf00175161
|View full text |Cite
|
Sign up to set email alerts
|

Improved detection of a staphylococcal infection by monomeric and protein A-purified polyclonal human immunoglobulin

Abstract: The present study was undertaken to compare the technetium-99m labelled non-specific polyclonal human immunoglobulin (Ig) with 99mTc-labelled monomeric human immunoglobulin (m-Ig), 99mTc-labelled, protein A-purified, human immunoglobulin (A-Ig) and 99mTc-labelled monomeric, protein A-purified, human immunoglobulin (mA-Ig) as tracer agents for the detection of a thigh infection with Staphylococcus aureus. In vitro the binding of the various tracer agents to bacteria at various intervals was determined. For the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
3

Year Published

1994
1994
2011
2011

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 7 publications
0
14
0
3
Order By: Relevance
“…In the thigh infection model, it was demonstrated that shortly after injection, Tc-labeled IgG, lower T/NT values as observed at intervals from 4 h on might be explained by the reduction in bacterial number induced by HNP-1, because an increase in the accumulation of IgG is related to the outgrowth of bacteria present at the site of infection (9). The difference in molecular size between HNP-1 (mol wt ϭ 3500) and IgG (mol wt ϭ 150,000) is a plausible explanation for enabling small molecules to get easier access to infected sites (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the thigh infection model, it was demonstrated that shortly after injection, Tc-labeled IgG, lower T/NT values as observed at intervals from 4 h on might be explained by the reduction in bacterial number induced by HNP-1, because an increase in the accumulation of IgG is related to the outgrowth of bacteria present at the site of infection (9). The difference in molecular size between HNP-1 (mol wt ϭ 3500) and IgG (mol wt ϭ 150,000) is a plausible explanation for enabling small molecules to get easier access to infected sites (15).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, to study accumulation of HNP-1 at the site of infection and its biodistribution in various organs, 99m Technetium ( 99m Tc)-labeled HNP-1 was used in experimental Klebsiella pneumoniae (gram-negative) or S. aureus (gram-positive) thigh infections. These results were compared with those obtained using 99m Tc-IgG, an established marker for infection (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Conflicting evidence has been presented on the role of vascular permeability in the process (Fischman et al 1988a;Morrel et al 1989;Rubin et al 1989a;Thakur et al 1990;Calame et al 1991). Furthermore, it could not be demonstrated that binding of the Fc part of IgG to phagocytes accounts exclusively for this mechanism (Fischman et al 1988a(Fischman et al , 1990Rubin et al 1989a;Calame et al 1991).…”
Section: Introductionmentioning
confidence: 87%
“…Box 7161, NL-1007 MC Amsterdam, The Netherlands Offprint requests to: E.K.J. Pauwels for 111In (Fischman et al 1988a;Rubin et al 1989a;Oyen et al 1990) as well as 99mTc (Blok et al 1990; Buscombe et al 1990;Calame et al 1991). However, the mechanism responsible for this accumulation at the site of infection has not yet been clarified.…”
Section: Introductionmentioning
confidence: 93%
“…The presently available radiopharmaceuticals are often incapable of determining between sterile inflammation and infection. Many pharmaceuticals labeled with different radioisotopes, such as immunoglobulins [1,2], liposomes labeled with 99m Tc [3], the avidin-biotin system [4], antigranulocyte antibodies and antibody fragments, chemotactic peptides, cytokines, interleukins, platelet factor 4, and ciprofloxacin labeled with 99m Tc [5] have been used, but an optimal agent has not yet been found. Thus, autologous leukocytes labeled with 111 In or 99m Tchexamethylpropyleneamine oxime are still considered the gold standard despite the practical limitations of considerable time and labor for preparation and the necessity of a sterile environment [6].…”
Section: Introductionmentioning
confidence: 99%